Laser-induced breakdown spectroscopy as a readout method for immunocytochemistry with upconversion nanoparticles - Pořízka, Pavel; Vytisková, Karolína; Obořilová, Radka; Pastucha, Matěj; Gábriš, Ivo; Brandmeier, Julian C; Modlitbová, Pavlína; Gorris, Hans H; Novotný, Karel; Skládal, Petr; Kaiser, Jozef; Farka, Zdeněk (Mikrochimica acta, 2021)
Immunohistochemistry (IHC) and immunocytochemistry (ICC) are widely used to identify cancerous cells within tissues and cell cultures. Even though the optical microscopy evaluation is considered the gold standard, the limited range of useful labels and narrow multiplexing capabilities create an imminent need for alternative readout techniques. Laser-induced breakdown spectroscopy (LIBS) enables large-scale multi-elemental analysis of the surface of biological samples, e.g., thin section or cell pellet. It is, therefore, a potential alternative for IHC and ICC readout of various labels or tags (Tag-LIBS approach). Here, we introduce Tag-LIBS as a method for the specific determination of HER2 biomarker. The cell pellets were labeled with streptavidin-conjugated upconversion nanoparticles (UCNP) through a primary anti-HER2 antibody and a biotinylated secondary antibody. The LIBS scanning enabled detecting the characteristic elemental signature of yttrium as a principal constituent of UCNP, thus indirectly providing a reliable way to differentiate between HER2-positive BT-474 cells and HER2-negative MDA-MB-231 cells. The comparison of results with upconversion optical microscopy and luminescence intensity scanning confirmed that LIBS is a promising alternative for the IHC and ICC readout.
Keywords: nádorové buněčné linie; Antibodies, Immobilized; Receptor, ErbB-2; Laser-induced breakdown spectroscopy; Light; Nanoparticles; Yttrium; imunohistochemie; receptor erbB-2; Immunocytochemistry; thulium; světlo; Cell Line, Tumor; imobilizační protilátky; Photon-upconversion nanoparticles; studie proveditelnosti; Biomarkers, Tumor; spektrální analýza; Immunohistochemistry; Thulium; nádorové biomarkery; Humans; ytrium; Fluorides; nanočástice; Spectrum Analysis; fluoridy; Feasibility Studies; lidé; Tag-LIBS